Early Warning System and Crisis Management - Riani, Ririn; Ikhwan, Ihsanul (SMART Insight, 2023)
This research was made to find out the development map on the research topic with the theme Early Warning Economic Crisis. This study discusses bibliometric mapping of the development of trends in keywords, authors, and journals on digital banking from a number of Scopus-indexed reputable papers published between 1990 and 2021. Early warning systems help organizations reduce losses and are critical in detecting emergencies from occurring. This research contributes to the field of early warning system development and applications in the economic and financial sectors by providing new knowledge and critical insights into a previously unexplored topic. Our research also contributes to a better understanding of the use of Early warning systems in business, finance, and economics. Consequently, accumulating knowledge to detect risks before it is too late is crucial for companies to maintain a competitive advantage in the market.